1953
DOI: 10.1021/ja01111a055
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalyzed Decomposition of Cumene Hydroperoxide

Abstract: Investigation of the kinetics of the acid-catalyzed, degradative rearrangement of cumene hydroperoxide to phenol and acetone in aqueous acetic acid containing varying amounts of ^-toluenesulfonic acid has shown the reaction to be first order with respect both to the hydroperoxide and to hydronium ion. It is not catalyzed by molecular acetic acid. The over-all activation energy for the decomposition in fifty weight per cent, acetic acid at unit ionic strength is 21.3 kcal./mole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1955
1955
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…The peroxide levels found in our study would be high enough to explain their observations of H 2 O 2 . Acid catalysed decomposition has been shown to be rather slow (Miner and Hagan, 1972;Seubold and Vaughan, 1953). Based on those data, we estimate that the decomposition of the reactive peroxides by hydronium ions would be below 5 % within 60 min.…”
Section: Soa From Photo-oxidation Of α-Pinenementioning
confidence: 97%
“…The peroxide levels found in our study would be high enough to explain their observations of H 2 O 2 . Acid catalysed decomposition has been shown to be rather slow (Miner and Hagan, 1972;Seubold and Vaughan, 1953). Based on those data, we estimate that the decomposition of the reactive peroxides by hydronium ions would be below 5 % within 60 min.…”
Section: Soa From Photo-oxidation Of α-Pinenementioning
confidence: 97%
“…The effect of acid activation, catalyst quantity, concentration of CHP and temperature were optimized using activated bentonite catalyst. An ionic decomposition mechanism has been suggested for the decomposition of CHP by bentonite catalyst (Scheme 2), which is analogous to a mechanism reported in the literature [16]. The formation of byproducts depends on the strength of the acid catalyst and the reaction conditions such as temperature.…”
Section: Catalytic Studiesmentioning
confidence: 87%
“…The formation of byproducts depends on the strength of the acid catalyst and the reaction conditions such as temperature. In the presence of strong acid such as sulfuric acid at relatively high temperature, one can expect the minor olefinic product, a-methylstyrene through elimination [16]. The change in the strength of the catalyst as well as the reaction temperature changes the selectivity of the reaction products during the decomposition of CHP.…”
Section: Catalytic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The requirement of both an acid and a free-radical source for the initiation of polymerization appears to be another example of a growing class of hybrid s y s t e d in which the free-radical and ionic stages are cooperatively involved, such as some Zeigler types of polymerization2* and those recently described by Okamura et al 26 Another method of producing high polymer from a-phenylethylisonitrile was found to be accomplished by simply warming in air at 50°C. for several days monomer that which had been seeded w-ith polymer produced by the ground-glass catalyst system.…”
Section: Initiation Of Polymerization Of A-phenylethylisonitrilementioning
confidence: 98%